A CONCEPTUAL DESIGN OF SECONDARY PADDING OF CHILD HELMET USING SWIMMING TUBE - Akmal, S.; Fauadi, M.H.F.M.; Hambali, R.H.; Hadzlin, N.; Taufik, R.S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Due to unavailability of a helmet that is below 57 cm in diameter, this paper presents the design of a child’s helmet that has the flexibility to suit any head diameter size of children in Malaysia. The target group of this proposed helmet is children from 2-6 years old. The scoring concept was used to select the proposed design. It reuses the conventional kid helmet structure in the market by making sure the re-processing of broken swimming tubing material. The unique characteristic that tube has is the ability to inflate and in this paper, is called as secondary padding that located in the inner shell of a proposed helmet. A finite element analysis using SolidWorks software was conducted for evaluating the static analysis of secondary padding which includes stress, displacement, and strain. The results show that the secondary padding using swimming tube design is safe to use with the condition of 8.357e6 N/m2 maximum von Mises stress with a safety factor of 1.523.